THE EFFECTS OF TRAINING METHODS AND BALANCE TO SUN BACK (SMASH KEDENG) IN SEPAK TAKRAW OF UNIVERSITY STUDENTS (FEMALE) AT KADER BANGSA UNIVERSITY PALEMBANG - LESTARI, HIKMAH (Jurnal Dosen Universitas PGRI Palembang)
ABSTRACTThe purpose of this study is to determine the effect of the methods maxex training & plyometric and balance to sun back (smash kedeng) in sepak takraw. The research is conducted of university students (female) at Kader Bangsa University Palembang. This study uses treatment by level 2 x 2. The samples are consisted of 36 university students (female). The technique of data analysis is two ways analysis of variance (ANAVA) and followed by Tukeys test at significance level of Î± = 0.05. The results of this study show that (1) method of maxex training has a better effect than method of plyometric to sun back (smash kedeng) insepak takraw of university students (female) at Kader Bangsa University Palembang; (2) there is an interaction between method of maxex training, method of plyometric and balance to sun back (smash kedeng) in sepak takraw of university students (female) at Kader BangsaUniversity Palembang; (3) method of maxex training have a better effect than method of plyometric and high balance to sun back (smash kedeng) in sepak takraw of university students (female) at Kader Bangsa University Palembang; 4) method of plyometric have abetter effect than method of maxex training and low balance to sun back (smash kedeng) in sepak takraw of university students (female) at Kader Bangsa University Palembang.Keyword: Methods Maxex Training and Plyometric, Balance, To sun back (smash kedeng) insepak takraw